Interview Sequences and the Formation of Subjective Assessments - Jonas Radbruch; Amelie Schiprowski (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
Interviewing is a decisive stage of most processes that match candidates to firms or organizations. This paper studies how the interview assessment of a candidate depends on the other candidates seen by the same evaluator, and their relative timing in particular. We leverage novel administrative data covering about 29,000 one-to-one interviews conducted within the admission process of a prestigious study grant program. Identification relies on the quasi-random assignment of candidates to evaluators and time slots.We find that a candidate's assessment decreases when her evaluator receives a better candidate draw.Moreover, the influence of the previous candidate is about three times stronger than the influence of the average other candidate in the sequence. The empirical pattern suggests that evaluators exhibit a contrast effect caused by the interplay between the associative recall of prior candidates and the attention to salient quality differences.
Keywords: 330